Quantifying capacity of otolaryngology‐head and neck surgery in Zimbabwe - Katerina J. Green; Daniel G. Eyassu; Amiti Jain; Priya Arya; Estephania Candelo; Dontre' M. Douse; Naboth N. Matinhira; Clemence Chidziva; Joshua P. Wiedermann (Laryngoscope Investigative Otolaryngology, 2025)
Abstract Objective(s) To evaluate the otolaryngology surgical capacity in Harare, Zimbabwe by analyzing procedural volumes across four hospitals, one private and three public, from 2019 to 2022. Methods A retrospective review of hand‐written surgical case logs was conducted at Harare Eye, Ear, Nose, and Throat Institute (HEENT), Parirenyatwa Group of Hospitals (PGH), Sally Mugabe Children's Hospital (SMCH), and Sally Mugabe Adult's Hospital (SMAH). Patient age and surgical intervention for all otolaryngology surgeries performed in the operating room from 2019 to 2022 were recorded. Procedures were categorized into six groups: head and neck malignancy, laryngeal surgery, oropharyngeal surgery, otologic surgery, rhinology/sinus surgery, and other. Data were analyzed using descriptive statistics to identify trends in surgical volume and types of procedures across hospitals. Results A total of 2626 procedures were recorded: 1470 at HEENT, 377 at PGH, 625 at SMCH, and 154 at SMAH. Of these, 39.5% were performed on pediatric patients and 60.5% on adult patients. The most common procedures were adenotonsillectomy/adenoidectomy/tonsillectomy (38.9%), diagnostic endoscopies (10.4%), and endoscopic sinus surgery (8.3%). HEENT performed the highest volume and widest range of procedures. HEENT had higher surgical volumes across all groups of procedure, except for laryngeal surgery. Conclusion This study found disparities in otolaryngology surgical capacity between a private hospital, HEENT, and three public tertiary hospitals—SMCH, SMAH, and PGH, the largest hospital in the country—in Harare, Zimbabwe. Additionally, it highlights areas for targeted interventions in capacity building. This study establishes a foundation for understanding otolaryngologic surgical capacity in the country, supporting international collaboration, guiding future research, and serving as a model for similar assessments in other LMICs. Level of evidence Level VI.